Model-Informed Repurposing of Medicines for SARS-CoV-2: Extrapolation of Antiviral Activity and Dose Rationale for Paediatric Patients - Federico Romano; Salvatore D’Agate; Oscar Della Pasqua (Pharmaceutics, 2021)
Repurposing of remdesivir and other drugs with potential antiviral activity has been the basis of numerous clinical trials aimed at SARS-CoV-2 infection in adults. However, expeditiously designed trials without careful consideration of dose rationale have often resulted in treatment failure and toxicity in the target patient population, which includes not only adults but also children. Here we show how paediatric regimens can be identified using pharmacokinetic-pharmacodynamic (PKPD) principles to establish the target exposure and evaluate the implications of dose selection for early and late intervention. Using in vitro data describing the antiviral activity and published pharmacokinetic data for the agents of interest, we apply a model-based approach to assess the exposure range required for adequate viral clearance and eradication. Pharmacokinetic parameter estimates were subsequently used with clinical trial simulations to characterise the probability target attainment (PTA) associated with enhanced antiviral activity in the lungs. Our analysis shows that neither remdesivir, nor anti-malarial drugs can achieve the desirable target exposure range based on a mg/kg dosing regimen, due to a limited safety margin and high concentrations needed to ensure the required PTA. To date, there has been limited focus on suitable interventions for children affected by COVID-19. Most clinical trials have defined doses selection criteria empirically, without thorough evaluation of the PTA. The current results illustrate how model-based approaches can be used for the integration of clinical and nonclinical data, providing a robust framework for assessing the probability of pharmacological success and consequently the dose rationale for antiviral drugs for the treatment of SARS-CoV-2 infection in children.